Carbon composite active material, electrode, secondary battery

CN123036685APending Publication Date: 2026-11-03KYOCERA CORP
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202480090323.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-29
Filing Date
2024-12-16
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

The discharge characteristics (rate characteristics) of existing lithium-ion secondary batteries at high current values ​​have not been sufficiently improved, and insufficient or excessive heating treatment of graphene as a conductive additive will affect electronic conductivity and discharge capacity.

Method used

The material is a carbon composite active material, in which the graphene material contains anionic functional groups and countercations at the ends. The ratio of the D and G band peak intensities (ID/IG) in the Raman spectrophotometer is less than 0.50. The graphene material content is 0.1-2.2% by mass, and the binder content is 0.01-0.7% by mass. An electronic conduction network is formed through mechanical composite.

Benefits of technology

It improves the rate capability and electronic conductivity of the secondary battery, reduces internal resistance, and maintains good battery characteristics.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_3
    Figure SMS_3
  • Figure SMS_4
    Figure SMS_4
Patent Text Reader

Abstract

A carbon composite active material having particles of an electrode active material and a surface layer covering the particles, wherein the surface layer is composed of a coating material containing a graphene material and a binder, the graphene material contains an anionic functional group and a counter cation of the anionic functional group at a terminal end, and a peak intensity ratio (I D / I G ) of a D band and a G band of a Raman spectrum obtained by Raman spectroscopy is 0.50 or less, in the carbon composite active material, a content of the graphene material is 0.1 to 2.2 mass%, and a content of the binder is 0.01 to 0.7 mass%.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure relates to carbon composite active material materials, electrodes, and secondary batteries. Background Technology

[0002] With the miniaturization and lightweighting of electronic materials and the development of HEVs or EVs, there is a demand for miniaturization or increased capacity of secondary batteries, which serve as their power source. In the secondary battery sector, various technologies have been developed for lithium-ion secondary batteries, which offer advantages such as high voltage and high energy density.

[0003] Patent Document 1 discloses the following technology: a composite material is used as the positive electrode active material in a lithium-ion secondary battery, in which a large number of carbon material particles (such as acetylene black) are attached to the surface of a phosphate compound as a conductive additive, and the specific surface area per unit mass of the positive electrode active material is set to a size of more than a specified value. Phosphate compounds have advantages such as high safety, but on the other hand, they have the problem of low electronic conductivity. However, it has been reported that in the aforementioned composite material, the contact area between the positive electrode active material and the conductive additive is increased, and the electronic conductivity is improved.

[0004] However, acetylene black consists of large particles with an average particle size of tens to hundreds of nm, resulting in point contacts with high contact resistance when they come into contact with the active material. In the active material layer where the active material and conductive additive are interconnected through point contacts, it is difficult to form a network for electron conduction, leading to low electronic conductivity. To improve electronic conductivity, the amount of conductive additive needs to be increased to increase the number of contact points. However, increasing the amount of conductive additive reduces the ratio of active material in the electrode, resulting in a decrease in the discharge capacity of the secondary battery using this electrode.

[0005] Patent Document 2 discloses a technique that uses graphene as a conductive additive in the positive electrode active material layer. In the positive electrode active material layer where graphene is used as a conductive additive, graphene and the active material, as well as graphene and graphene, are interconnected through surface contacts to form an electronic conduction network. Because the active material layer with conductive paths connected by surface contacts has high electronic conductivity, it is not necessary to increase the amount of conductive additive to improve electronic conductivity as in Patent Document 1, thus avoiding the problem of reduced discharge capacity caused by an increase in the amount of conductive additive.

[0006] Patent Document 2 teaches that in order to use graphene as a conductive additive and form an electron-conducting network in the positive electrode active material layer, the graphene must first be uniformly dispersed in a dispersion medium. It discloses a method of preparing a positive electrode paste by adding graphene oxide, active material, and binder together to the dispersion medium, followed by heat treatment to reduce the dispersed graphene oxide back to graphene. In the resulting positive electrode active material layer, an electron-conducting network is formed within the active material layer, exhibiting excellent electron conductivity. On the other hand, it discloses that for positive electrode active material layers prepared by adding graphene as a conductive additive, along with the active material and binder, to the dispersion medium, the dispersion is insufficient. As a result, an electron-conducting network cannot be formed within the positive electrode active material layer. The same result is achieved when graphene, which is a reduced form of graphene oxide, is added to the dispersion medium instead of graphene as a conductive additive. In other words, Patent Document 2 is a technology that requires the following process: after producing a positive electrode paste using graphene oxide, a heat treatment is performed to remove the oxygen contained in the graphene oxide, thereby forming a positive electrode active material layer containing graphene.

[0007] In the technology of Patent Document 2, which requires the aforementioned heat treatment, if the heat treatment is insufficient, more residual oxygen will remain, making it impossible to form a sufficient electronic conduction network, resulting in a decrease in electronic conductivity. Excessive heat treatment becomes the main cause of deterioration of the active material and decomposition of the binder, resulting in a decrease in discharge capacity.

[0008] Existing technical documents

[0009] Patent documents

[0010] Patent document 1: Japanese Patent Application Publication No. 2002-110162.

[0011] Patent Document 2: Japanese Patent Application Publication No. 2020-21745. Summary of the Invention

[0012] The problem that the invention aims to solve

[0013] In recent years, there has been a demand for improved rate performance, i.e. discharge performance at high current values, in secondary batteries. Neither of the technologies in patent documents 1 and 2 has yet achieved sufficient rate performance.

[0014] This disclosure was made in view of the above-mentioned circumstances, and its purpose is to provide carbon composite active material materials and related technologies that can improve the rate characteristics of secondary batteries.

[0015] Methods for solving problems

[0016] To achieve the aforementioned objectives, this disclosure provides the following means.

[0017] <Carbon Composite Active Material Materials>

[0018] [1] A carbon composite active material having particles of an electrode active material and a surface layer coating the particles, wherein the surface layer is composed of a coating material comprising graphene material and a binder, the graphene material comprising anionic functional groups and countercations of the anionic functional groups at its ends, and the peak intensity ratio of the D band and the G band of the Raman spectrophotometer obtained by Raman spectroscopy is (I D / I G The content of the graphene material is 0.1 to 2.2% by mass, and the content of the binder is 0.01 to 0.7% by mass.

[0019] [2] According to the carbon composite active material of [1], the content ratio of the aforementioned graphene material to the aforementioned binder is 3 to 30.

[0020] [3] According to the carbon composite active material of [1] or [2], the ratio of the surface dimension DG of the aforementioned graphene material to the particle size DA of the aforementioned electrode active material (DG / DA) is 0.002 to 3.000.

[0021] [4] The carbon composite active material according to any one of [1] to [3], wherein the aforementioned electrode active material is a positive electrode active material.

[0022] [5] The carbon composite active material according to any one of [1] to [4], wherein the aforementioned electrode active material is a negative electrode active material.

[0023] [6] According to the carbon composite active material of [4], the aforementioned positive electrode active material is a lithium-containing composite oxide.

[0024] [7] According to the carbon composite active material of [6], wherein the aforementioned lithium-containing composite oxide has at least one crystal structure selected from the group consisting of olivine type, layered rock salt type and spinel type.

[0025] [8] According to the carbon composite active material in [5], the aforementioned negative electrode active material is selected from graphite, SiO2, etc. x (0≤x<2) and at least one of the group consisting of lithium titanate.

[0026] [9] A carbon composite active material according to any one of [1] to [8], wherein the aforementioned binder comprises at least one selected from the group consisting of fluorinated resins, olefin resins, vinyl resins, polyamides, polyimides, polyethers, polysaccharides and rubbers.

[0027] <Electrode>

[0028]

[10] An electrode, wherein it is formed from a slurry containing a carbon composite active material comprising any one of [1] to [9].

[0029] Secondary batteries

[0030]

[11] A secondary battery having electrodes of

[10] .

[0031] Invention Effects

[0032] According to this disclosure, a carbon composite active material can be provided that can improve the rate characteristics of a secondary battery. Detailed Implementation

[0033] The present disclosure will now be described in detail with reference to one embodiment.

[0034] In this specification, "XX~YY" refers to "above XX and below YY". Furthermore, in this specification, the lower and upper limits of numerical ranges (e.g., ranges of content) can be independently combined. Additionally, the upper or lower limit of the numerical ranges described in this specification can be replaced with the values ​​shown in the examples.

[0035] [Carbon composite active material materials]

[0036] The carbon composite active material disclosed herein is a carbon composite active material having particles of electrode active material and a surface layer coating the aforementioned particles. The aforementioned surface layer is composed of a coating material containing graphene material and a binder. The aforementioned graphene material contains anionic functional groups and countercations of the anionic functional groups at its ends. Furthermore, the peak intensity ratio (ID) of the D band and G band of the Raman spectrophotometer obtained by Raman spectroscopy is... D / I G The content of the graphene material is 0.1 to 2.2% by mass, and the content of the binder is 0.01 to 0.7% by mass.

[0037] <Graphene Materials>

[0038] The graphene material contained in the surface layer of the carbon composite active material disclosed herein is a graphene material formed by introducing modifying groups into graphene serving as the parent material. Specifically, the aforementioned graphene material contains anionic functional groups and countercations of the anionic functional groups at its ends, and its Raman spectra are located in the range of 1300–1400 cm⁻¹. -1 The peak intensity of the D band within the range of I D With a height of 1550-1650cm-1 The peak intensity of the G-band within the range of I G Peak intensity ratio (I) D / I G () refers to graphene materials with a thickness of less than 0.50.

[0039] From the perspective of improving ionic conductivity, graphene materials preferably possess a certain degree of structural defects. If graphene materials contain structural defects, ions can move through these defects, thus improving ionic conductivity. On the other hand, if graphene materials have too many structural defects, they become low conductive.

[0040] Structural defects in graphene materials can be determined using Raman spectroscopy. The D band represents peaks originating from defects in the graphene material, while the G band represents peaks originating from the graphite structure. The I band does not normally appear in fully crystalline graphite. D The peak, but with the loss of symmetry in the graphite structure, I D As peak intensity increases, if the graphene material has more structural defects, the peak intensity ratio (I0) will increase. D / I G It also gets bigger.

[0041] By using a counter cation containing an anionic functional group at the end and that anionic functional group, and the aforementioned peak intensity ratio (I) D / I G Using graphene materials with a thickness of less than 0.50 as conductive additives can balance ionic conductivity and electrical conductivity.

[0042] Peak intensity ratio (I) D / I G The lower limit is not specified, but from the perspective of current manufacturing technology, it can be above 0.10.

[0043] Peak intensity ratio (I) D / I G The value can be 0.10 to 0.50, 0.11 to 0.40, or 0.12 to 0.30.

[0044] It should be noted that the aforementioned peak intensity ratios are all measured using a solid-state laser as the excitation laser at an excitation wavelength of 514.79 nm. In Raman spectroscopy, graphene powder at 1570 cm⁻¹... -1 Nearby and 1345cm -1 There are peaks nearby.

[0045] (graphene)

[0046] In this disclosure, graphene refers to graphene with a thickness of a single atom. 2A sheet-like material consisting of stacked sheets of bonded carbon atoms (monolayer graphene). The number of stacked layers can be less than 100, less than 50, or less than 20.

[0047] The average particle size of graphene is not particularly limited; from a dispersibility point of view, it can be 0.5–15 μm, 1.0–10 μm, or 1.5–5 μm. In this disclosure, the average particle size of graphene refers to the particle size that, relative to the particle size distribution, constitutes 50% of the total particle size (D50). The average particle size of graphene can be measured using a laser diffraction type particle size analyzer (e.g., MT3300EXII, manufactured by Microtrac BEL Co., Ltd., Japan).

[0048] Graphene with the aforementioned average particle size can be obtained by pulverizing carbon materials with a particle size of 1–700 μm using a known pulverizing device. The aforementioned carbon material can be 3–500 μm, 5–300 μm, or 10–200 μm. Known pulverizing devices include, for example, dry pulverizing devices such as ball mills, planetary mills, stirred mills, bead mills, jet mills, hammer mills, and high-speed mixers, as well as ball mills, planetary mills, stirred mills, and bead mills that utilize media. From the viewpoint of improving productivity, a high stirring speed and a short stirring time are preferred.

[0049] There is no particular limit to the carbon atom content in graphene; it can be 95% or more by mass, 99% or more by mass, or 100% by mass.

[0050] The content of impurities in graphene is not particularly limited; it can be less than 5% by mass, less than 1% by mass, or even 0% by mass.

[0051] From a dispersive perspective, the thickness of graphene can be 0.3–60.0 nm, 0.3–30.0 nm, or 0.6–12.0 nm.

[0052] The "thickness" mentioned here refers to the thickness of a single layer in the case of a single layer, and to the overall thickness of the layers in the case of multiple layers.

[0053] The thickness of graphene can be measured, for example, using an atomic force microscope.

[0054] (Modifying group)

[0055] In graphene materials, the modifying groups introduced into the graphene that serves as the parent material consist of anionic functional groups and countercations of those anionic functional groups.

[0056] It is inferred that in the aforementioned modified groups, anionic functional groups are bonded to the ends of graphene particles, counteracting the attraction of cations to the surrounding negatively charged graphene.

[0057] As described later, during the manufacturing of graphene materials, the graphene is pulverized, and free radicals are generated at the fracture surface during this process. It is believed that through the free radicals generated at the graphene fracture surface and the weak acid reaction forming a weak acid, the counter anion of the water-soluble salt bonds with the graphene. This bonding can be any of the following: covalent, ionic, or coordination bonds. Alternatively, it can involve the physical adsorption of the water-soluble salt component onto the carbon material.

[0058] The mechanical energy generated during the crushing process promotes the reaction and bonding of free radicals generated at the fracture surface of graphene with weak acid salts (such as lithium acetate).

[0059] If a solvent is added to a graphene material in which modified groups have been incorporated, the aforementioned countercations dissociate in the solvent, and electrostatic repulsion acts on the graphene bonded to anionic functional groups. Therefore, this graphene material exhibits good dispersibility in the solvent and is difficult to re-aggregate.

[0060] By bonding anionic modifiers to graphene, it exhibits a high degree of negative charge in the dispersion. If the negative charge increases, the dispersibility properties described later become higher. General-purpose graphene (e.g., commercially available graphene nanosheets (XGsciense, trade name: R10)) and only pulverized graphite have small negative charges, and van der Waals forces dominate, thus resulting in lower dispersibility properties through aggregation.

[0061] From the perspective of the anionic functional group's ability to counteract the dissociation of cations, the anionic functional group constituting the modifying group can be at least one selected from the group consisting of carboxyl, carbonate, sulfonic acid, and phosphate groups, or it can be a carboxyl or carbonate group.

[0062] From the perspective of ionization trend, the counter cation constituting the modifying group can be selected from at least one of the group consisting of potassium ion, sodium ion, lithium ion, barium ion, calcium ion, magnesium ion, rubidium ion and ammonium ion, or it can be potassium ion, lithium ion and sodium ion.

[0063] When the modifying group consists of an anionic functional group and a countercation of that anionic functional group, the concentration of the countercation in the graphene material can be 50–15000 ppm by mass, 50–13000 ppm by mass, 50–10000 ppm by mass, 50–5000 ppm by mass, or 100–5000 ppm by mass. If the concentration of the countercation is above 50 ppm by mass, the dispersibility of the graphene material in the solvent can be further improved. If it is below 15000 ppm by mass, the electrostatic repulsion acting on the graphene material in the solvent becomes stronger, thus the graphene material can be further maintained in a dispersed state in the solvent.

[0064] The concentration of countercations contained in graphene materials can be determined by ICP-OES (Inductively Coupled Plasma Optical Emission Spectrometry) and ICP-MS (Inductively Coupled Plasma Mass Spectrometry). Specifically, it can be determined by the methods described in the examples.

[0065] (pH)

[0066] The pH (25°C) of the dispersion obtained by dispersing graphene material (concentration: 0.3% by mass) in a mixed solvent containing deionized water and 2-propanol in a volume ratio of 6:4 can be 5.1 to 8.1, 5.5 to 8.0, or 6.0 to 7.9.

[0067] For graphene materials with modifying groups consisting of anionic functional groups and countercations of those anionic functional groups, when the pH is within the aforementioned range, the countercations readily dissociate in the solvent, and the anionic functional groups readily become charged. Consequently, electrostatic repulsion acts on the graphene bonded to the anionic functional groups, thus further improving the dispersibility of the graphene material in the solvent and making it difficult for it to re-aggregate.

[0068] pH can be set within the above range by appropriately adjusting the properties of graphene, the type of water-soluble salt, the ratio of graphene to water-soluble salt, and the mixing and pulverizing conditions.

[0069] (particle size)

[0070] In the cumulative particle size distribution on a volume basis determined by laser diffraction scattering, the cumulative 50% particle size (D50) of graphene material from the small particle side can be 0.5 to 15.0 μm.

[0071] If the particle size (D50) is above 0.5 μm, the crystallinity of the graphene material is easily maintained, and the dispersibility is improved. If the particle size (D50) is below 15.0 μm, the crystallinity of the graphene material is maintained, and the dispersibility is improved. The particle size (D50) can be 1.0–10.0 μm or 1.5–5.0 μm.

[0072] (Dispersed Indicators)

[0073] For graphene materials, the dispersion index calculated by the following <Equation 1> can be 20-70%.

[0074] <Formula 1>

[0075] Dispersion index (X) [%] = [(Absorbance) / (Absorbance coefficient × Unit thickness) / (Initial concentration)] × 100

[0076] (In Equation 1, the absorbance coefficient is 3200 (L / g·m), the unit thickness is 0.0001 (m), and the initial concentration is the solid component concentration when the graphene material is dispersed in a mixed solvent of deionized water and 2-propanol (IPA) with a volume ratio of deionized water:IPA=6:4, which is set to 3 (g / L).)

[0077] If the aforementioned dispersion index is above 20%, the graphene material exhibits good dispersibility. If the dispersion index is below 70%, maintaining the interparticle distance within the graphene material can reduce cohesion. The aforementioned dispersion index can be 25–65%, or 30–60%.

[0078] The aforementioned dispersion parameters can be set within the above range by appropriately adjusting the average particle size of the carbon material used as the parent material, the concentration of water-soluble salts, the pH of the solvent, and the conductivity of the solvent.

[0079] In graphene materials, the larger the absolute value of the Zeta potential, the greater the electrostatic repulsion between graphene materials, and the more stable the dispersion. From the perspective of further improving the dispersion of graphene materials, the absolute value of the Zeta potential can be 30–60 mV, 30–55 mV, or 30–50 mV.

[0080] (Methods for manufacturing graphene materials)

[0081] One method for manufacturing graphene materials is to add water-soluble salts to graphene, mix them dry, and then wash the resulting mixture with water.

[0082] Anions released from water-soluble salts bond with graphene and enter the graphene, thereby promoting the exfoliation and fragmentation of the graphene. It should be noted that, in this disclosure, "fragmentation" is not limited to breaking or disintegrating the graphene into smaller pieces than the graphene used as a raw material, but also includes the purpose of simply breaking up the aggregates of graphene.

[0083] The graphene described above can be used.

[0084] There are no restrictions on the type of water-soluble salt, as long as it is soluble in water. Specific examples of water-soluble salts include tripotassium citrate, potassium tartrate, potassium acetate, potassium glutamate, potassium carbonate, and tripotassium phosphate. Furthermore, examples can be made by replacing the potassium in these water-soluble salts with salts of sodium, lithium, barium, calcium, magnesium, rubidium, and ammonium. One type of water-soluble salt can be used, or a combination of two or more can be used.

[0085] The amount of water-soluble salt relative to 100 parts by mass of carbon material can be 1–500 parts by mass, 10–400 parts by mass, or 100–300 parts by mass. When the amount of water-soluble salt is more than 1 part by mass, the dispersibility in the solvent is improved through the formation of graphene material. When the amount of water-soluble salt is less than 500 parts by mass, excessive reaction and adsorption of water-soluble salt can be reduced.

[0086] There are no particular limitations on the environmental conditions for mixing and pulverizing water-soluble salts and graphene. It can be carried out under similar environmental conditions as the aforementioned pulverization, i.e., at room temperature (25°C) in air, or in a nitrogen environment or an inactive gas environment such as argon. In addition, it can also be carried out under high or low temperature conditions, or under pressure or depressurization conditions, as needed.

[0087] Regarding the pulverizing apparatus and its examples, as mentioned above, known apparatus can be used without limitation. Examples include dry pulverizing apparatus such as ball mills, bead mills, jet mills, hammer mills, and high-speed mixers. The processing conditions can be appropriately adjusted according to the type and particle size of the carbonaceous material.

[0088] After mixing the water-soluble salt and graphene, the resulting mixture is washed with water. This removes any remaining water-soluble salt.

[0089] The amount of water added during washing is only sufficient to obtain a suspension; there is no particular limitation. Heating can also be performed as needed. For example, add water at a ratio of 10 to 10,000 times the combined mass of the water-soluble salt and carbon material, and mix and stir. The number of washes can be, for example, 2 to 10 times, or 2 to 8 times. The washing conditions can be appropriately set according to the type of graphene and water-soluble salt used.

[0090] After washing, a filter can be used for filtration and separation. The appropriate pore size for the filter is selected based on the intended use of the obtained graphene material. The resulting graphene material can be dried and extracted as a powder, dispersed in a liquid, or used as a paste. Drying can be performed by any method. For example, the graphene material can be dried using spray drying.

[0091] <Adhesive>

[0092] The binder contained in the surface layer of the carbon composite active material disclosed herein serves to connect and fix the electrode active material and the graphene material, and may include at least one selected from the group consisting of fluorinated resins, olefin resins, vinyl resins, polyamides, polyimides, polyethers, polysaccharides, and rubbers.

[0093] For example, it can also be fluoropolymers such as polyvinylidene fluoride (PVDF), polyvinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), polytetrafluoroethylene (PTFE), and ethylene-tetrafluoroethylene copolymer (ETFE); olefin resins such as polyethylene (PE) and polypropylene (PP); vinyl resins such as polyvinyl alcohol (PVA), polyvinylpyrrolidone (PVP), polyacrylic acid (PAA), and lithium polyacrylate (LiPAA); polyamide (PA); polyimide (PI); polyethers such as polyethylene oxide (PEO); polysaccharides such as cellulose, carboxymethyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; and rubbers such as fluororubber, styrene-butadiene rubber (SBR), ethylene-propylene-diolefin rubber (EPDM), and sulfonated EPDM.

[0094] <Electrode Active Materials>

[0095] In the carbon composite active material disclosed herein, the electrode active material can be either a positive electrode active material or a negative electrode active material.

[0096] (Positive electrode active material)

[0097] The positive electrode active material can be a lithium-containing composite oxide.

[0098] The positive electrode active material can also be a lithium-containing composite oxide with at least one crystal structure selected from the group consisting of olivine type, layered rock salt type and spinel type.

[0099] Lithium-containing composite oxides with olivine-type structures can be composite oxides represented by the general formula LiMPO4 (where M is one or more of Fe(II), Mn(II), Co(II), and Ni(II)). Representative examples of the general formula LiMPO4 include LiFePO4, LiNiPO4, LiCoPO4, LiMnPO4, and LiFe... a Ni bPO4, LiFe a Co b PO4, LiFe a Mn b PO4, LiNi a Co b PO4, LiNi a Mn b PO4 (a+b is less than 1, 0<a<1, 0<b<1), LiFe c Ni d Co e PO4, LiFe c Ni d Mn e PO4, LiNi c Co d Mn e PO4 (c+d+e is less than 1, 0<c<1, 0<d<1, 0<e<1), LiFe f Ni g Co h Mn i PO4 (f+g+h+i is less than 1, 0<f<1, 0<g<1, 0<h<1, 0<i<1), etc.

[0100] Lithium-containing composite oxides with a layered rock salt-type crystal structure can be lithium cobalt oxide (LiCoO2), LiNiO2, LiMnO2, Li2MnO3, LiNi 0.8 Co 0.2 O2 and other NiCo-based compounds (general formula is LiNi) x Co 1-x O2 (0 < x < 1)), LiNi 0.5 Mn 0.5 O2 and other NiMn-based compounds (general formula is LiNi) x Mn 1-x O2 (0 < x < 1)), LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 O2 and other NiMnCo systems (also known as NMC. The general formula is LiNi). x Mn y Co 1-x-y O2 (x>0, y>0, x+y<1)). It can also be Li (Ni). 0.8 Co 0.15 Al 0.05 O2, Li2MnO3-LiMO2 (M=Co, Ni, Mn), etc.

[0101] Lithium-containing composite oxides with a spinel-type crystal structure can be LiMn2O4, Li 1+x Mn2-x O4, Li(MnAl)2O4, LiMn 1.5 Ni 0.5 O4.

[0102] In addition, the positive electrode active material can also be made of the general formula Li (2-j) MSiO4 (where M is one or more of Fe(II), Mn(II), Co(II), and Ni(II), 0 ≤ j ≤ 2) represents a composite oxide. As a general formula Li (2-j) A representative example of MSiO4 is Li. (2-j) FeSiO4, Li (2-j) NiSiO4, Li (2-j) CoSiO4, Li (2-j) MnSiO4, Li (2-j) Fe k Ni l SiO4, Li (2-j) Fe k Co l SiO4, Li (2-j) Fe k Mn l SiO4, Li (2-j) Ni k Co l SiO4, Li (2-j) Ni k Mn l SiO4 (k+l is less than 1, 0 < k < 1, 0 < l < 1), Li (2-j) Fe m Ni n Co q SiO4, Li (2-j) Fe m Ni n Mn q SiO4, Li (2-j) Ni m Co n Mn q SiO4 (m+n+q is less than 1, 0<m<1, 0<n<1, 0<q<1), Li (2-j) Fe r Ni s Co t Mn u SiO4 (r+s+t+u is less than 1, 0<r<1, 0<s<1, 0<t<1, 0<u<1), etc.

[0103] (Negative electrode active material)

[0104] The negative electrode active material can be carbon materials such as natural graphite, artificial graphite, mesophase carbon microspheres, mesophase carbon fiber (MCF), coke, glassy carbon, and sintered organic compounds; silicon-containing materials SiO2 x (0≤x<2), Sn, aluminum and other metals that can combine with lithium, alloys of these, composite materials of these metals and carbon materials, lithium titanate (Li4Ti5O) 12 Oxides such as SnO2 and metallic lithium. One of these can be used, or a combination of two or more.

[0105] The negative electrode active material can also be selected from materials including graphite and SiO2. x (0≤x<2) and at least one of the group consisting of lithium titanate.

[0106] There are no particular limitations on the shape of the active substance; examples include spherical, non-spherical, scaly, and plate-like shapes. Additionally, the active substance can also be a hollow particle with a void in the center.

[0107] When the active material is a particle, its average particle size can be greater than 1 nm and less than 100 μm, greater than 100 nm and less than 50 μm, or greater than 1000 nm and less than 25 μm.

[0108] It should be noted that the average particle size in this disclosure refers to the particle size D50, which, relative to the particle size distribution, represents 50% of the total particle size and can be measured by a laser diffraction particle size analyzer.

[0109] <Combination of Electrode Active Materials, Graphene Materials, and Binders>

[0110] The composite of electrode active material, graphene material and binder can be achieved by mechanically attaching graphene material and binder to the surface of electrode active material.

[0111] Mechanical adhesion refers to the repeated application of shear or compressive forces to a mixture of materials, causing the materials to adhere to each other. This is achieved through so-called mechanical compounding methods.

[0112] There are no particular limitations on the specific methods of mechanical compounding, as long as they are carried out using well-known compounding methods. This can be either dry compounding or wet compounding.

[0113] For example, after adding a binder and dispersing it in a deionized water / IPA solution composed of isopropanol and deionized water, graphene material is added, ultrasonically dispersed, and centrifuged to prepare a graphene dispersion. Active substances are mixed in the graphene dispersion, filtered, and dried to obtain a carbon composite active material.

[0114] In carbon composite active material materials, the content of the aforementioned graphene material can be 0.1 to 2.2% by mass, 0.1 to 2.0% by mass, or 0.1 to 0.5% by mass.

[0115] By setting the content of graphene materials with high conductivity and anionic functional groups within the above range, the local electronic and ionic conductivity of the surface of active material particles is improved.

[0116] In carbon composite active material, the content of the aforementioned binder can be 0.01 to 0.7% by mass, 0.01 to 0.25% by mass, or 0.01 to 0.06% by mass.

[0117] By setting the binder content within the aforementioned range, the effect of keeping the graphene material on the surface of the active material is ensured, and the reduction in battery characteristics caused by the loss of the reactive surface area of ​​the electrode active material is avoided, thereby maintaining good battery characteristics.

[0118] In carbon composite active material materials, the content ratio of the aforementioned graphene material to the aforementioned binder, by mass ratio, can be 3 to 30, 15 to 30, or 25 to 30.

[0119] If the content ratio is within the above range, the internal resistance (electron / lithium-ion moving resistance) of the secondary battery using the electrode formed by the carbon composite active material is reduced, and the rate performance is improved.

[0120] In the obtained carbon composite active material, the ratio of the surface dimension DG of the aforementioned graphene material to the particle size DA of the aforementioned electrode active material (DG / DA) can be 0.002 to 3.000, 0.003 to 0.400, or 0.020 to 0.100.

[0121] If the DG / DA ratio is below 3.000, it is easy to coat the surface of the particles of the electrode active material with graphene material. If the DG / DA ratio is above 0.002, the internal resistance (electron / lithium-ion moving resistance) of the secondary battery using the electrode formed by the carbon composite active material is reduced, thereby improving the rate performance.

[0122] The face dimension DG of the aforementioned graphene material refers to the face dimension, i.e., the long side of the graphene material in a plate shape. Specifically, it can be measured using the method described in the examples.

[0123] The particle size DA of the aforementioned electrode active material refers to the average of the longest and shortest diameters of the electrode active material particles. Specifically, it can be determined using the method described in the examples.

[0124] [electrode]

[0125] The electrode disclosed herein can be formed using a slurry containing a carbon composite active material. The composition and manufacturing method of the electrode are not particularly limited; any method already known may be used.

[0126] By using an electrode formed from a slurry containing the aforementioned carbon composite active material, the rate performance of the battery is improved. The structure of the electrode used to achieve this effect involves various forms; it is currently impossible or impractical to specify in detail one particular structure and fully express it in the present technology.

[0127] For example, the positive electrode for a lithium secondary battery according to one embodiment can be manufactured by coating a slurry obtained by mixing the aforementioned carbon composite active material, conductive additive, binder and solvent onto the positive electrode current collector and then drying it.

[0128] As a conductive additive, carbon materials such as Ketjen black, metallic materials such as Al, and conductive oxides can be used. As an adhesive, polyvinylidene fluoride, acrylic resins, and polytetrafluoroethylene resins can be used.

[0129] N-methylpyrrolidone and the like can be used as solvents. Metal thin films mainly containing aluminum can be used as positive electrode current collectors. The thickness of the positive electrode current collector is not particularly limited; for example, it can be set to 5–50 μm.

[0130] There are no particular limitations on the method of applying the paste to the current collector, and examples include doctor blade coating, dip coating, reverse roller coating, forward roller coating, gravure printing, extrusion, and brush coating. There are no particular limitations on the amount of paste applied; it can be appropriately set according to the desired thickness of the electrode composite layer.

[0131] There are no particular limitations on the method for drying the slurry on the current collector. Examples include drying based on warm air, hot air, or low-humidity air; vacuum drying; and drying based on (far)infrared radiation, electron beam irradiation, etc. Drying conditions can be appropriately set; for example, the drying temperature can be 50–250°C or 80–200°C. There are no particular limitations on the drying time, which is usually within the range of 10–60 minutes. The electrode can be stabilized by pressing it after drying. Pressing methods include die pressing and roller pressing, but are not limited to these.

[0132] [Rechargeable Battery]

[0133] The secondary battery of this disclosure has the aforementioned electrodes. In other words, in the secondary battery of this disclosure, at least one of the positive or negative electrodes is an electrode of this disclosure. The secondary battery of this disclosure has a high discharge capacity. When one of the positive or negative electrodes is an electrode of this disclosure and the other is not, the electrode of the other electrode is not particularly limited, and any electrode can be used.

[0134] Examples of secondary batteries disclosed herein include lithium-ion secondary batteries.

[0135] In addition to the electrodes described above, the secondary battery of this disclosure may also have an electrolyte layer. For example, the secondary battery of this disclosure is stacked with a positive electrode and a negative electrode facing each other, separated by an electrolyte layer.

[0136] The electrolyte layer can be composed of an electrolyte solution or a solid electrolyte. If the electrolyte layer is an electrolyte solution, it can also be a non-aqueous electrolyte solution formed by dissolving electrolyte salts in a non-aqueous solvent.

[0137] Examples of non-aqueous solvents include ethylene carbonate, fluoroethylene carbonate, chloroethylene carbonate, propylene carbonate, butene carbonate, vinylene carbonate, cyclopentanone, cyclohexylbenzene, sulfolane, propane sulpholactone, 3-methylsulfolane, 2,4-dimethylsulfolane, 3-methyl-1,3-oxazolidine-2-one, γ-butyrolactone, dimethyl carbonate, diethyl carbonate, methyl ethyl carbonate, methyl propyl carbonate, methyl butyl carbonate, ethyl propyl carbonate, ethyl butyl carbonate, dipropyl carbonate, 1,2-dimethoxyethane, tetrahydrofuran, 2-methyltetrahydrofuran, 1,3-dioxolane, methyl acetate, ethyl acetate, trimethyl phosphate, and triethyl phosphate. One or more of these can be used in combination.

[0138] Examples of electrolyte salts include lithium salts. There are no particular limitations on lithium salts as long as they are soluble in non-aqueous solvents and exhibit high ionic conductivity; they can be appropriately selected according to the purpose. Examples include lithium hexafluorophosphate (LiPF6) and lithium tetrafluoroborate (LiBF4).

[0139] The concentration of the electrolyte salt is not particularly limited and can be appropriately selected according to the purpose. From the viewpoint of lithium ion mobility and viscosity, in non-aqueous solvents, it can be 0.5 to 3.0 mol / L or 0.8 to 1.5 mol / L.

[0140] (spacer)

[0141] To prevent short circuits between the positive and negative terminals, a spacer is placed between them.

[0142] Materials used as spacers include, for example, kraft paper, vinylon blended paper, synthetic pulp blended paper, etc.; polyolefin nonwovens such as cellophane, polyethylene grafted film, polypropylene meltblown nonwoven fabric, polyamide nonwoven fabric, glass fiber nonwoven fabric, microporous membrane, etc.

[0143] The size of the spacer is not particularly limited as long as it can be used in an electrochemical element.

[0144] The spacer can be a single-layer structure or a stacked structure.

[0145] It should be noted that when using solid electrolytes, the spacer can be omitted.

[0146] The secondary battery disclosed herein exhibits excellent rate performance.

[0147] The secondary battery disclosed herein can retain a capacity of over 60.4% or even over 70% under 5C rate conditions.

[0148] Example

[0149] The present disclosure will now be described in detail through examples, but the present disclosure is not limited to these examples.

[0150] <The Production of Graphene Materials>

[0151] (Synthesis Example 1_Graphene Materials-1)

[0152] At room temperature (25°C) and in a nitrogen environment, 4g of natural graphite (ACB-50, manufactured by Nippon Graphite Industries, Ltd., average particle size 350μm) and 8g of potassium L-glutamate were pulverized for 40 minutes using a planetary ball mill (Fritsch, model: P-6, ball diameter 10mm, speed 540rpm). The pulverized material was then washed with deionized water, filtered, and dried at 60°C to obtain graphene material-1.

[0153] 0.3 g of the obtained graphene material-1 was added to 100 mL of a mixed solvent of deionized water and 2-propanol (IPA) (volume ratio: 60 / 40). The mixture was ultrasonically treated for 3 minutes using an ultrasonic homogenizer (UH-600S, manufactured by SMT Corporation, 26 mm Φ) to obtain a dispersion. The dispersion was sprayed onto a mica plate to prepare a test sample. The sample was observed using an atomic force microscope (AFM5300E, manufactured by Hitachi High-Tech Corporation, model number AFM5300E) to determine the thickness of the graphene material-1. The results confirmed a thickness of 0.99 nm, indicating that the number of graphene layers was less than 3, and that natural graphite was exfoliated between its layers to form graphene.

[0154] The obtained graphene material-1 was added to a platinum crucible for ashing, followed by alkali dissolution and dissolution in hydrochloric acid solution. It was then diluted with ultrapure water, and the target cations were quantitatively analyzed using an ICP-C spectrophotometer (Analytik Jena, Germany, model: PQ9000 Elite). The results confirmed the presence of potassium at 2200 ppm as a countercation.

[0155] (Synthesis Example 2_Graphene Materials-2)

[0156] At room temperature (25°C) and in a nitrogen environment, 4g of natural graphite (F#2, manufactured by Nippon Graphite Industries, Ltd., average particle size 130μm) and 8g of lithium acetate were weighed and pulverized in a planetary ball mill (manufactured by Feichi Corporation, model: P-6, ball diameter 10mm, speed 540rpm) for 40 minutes. Then, after washing with deionized water and filtering, the material was dried at 60°C to obtain graphene material-2.

[0157] The target cation was quantitatively analyzed using the same method as in Synthesis Example 1. The results confirmed the presence of lithium element at 3100 ppm by mass as a countercation.

[0158] (Synthesis Example 3_Graphene Materials-3)

[0159] At room temperature (25℃) and in a nitrogen environment, 4g of natural graphite (F#1, manufactured by Japan Graphite Industry Co., Ltd., average particle size 350μm), 8g of tripotassium citrate, and 25ml of IPA were weighed and pulverized in a planetary ball mill (manufactured by Feichi Company, model: P-6, ball diameter 10mm, speed 540rpm) for 40 minutes. Then, after washing with deionized water and filtering, the pulverized material was dried at 60℃ to obtain graphene material-3.

[0160] The target cation was quantitatively analyzed using the same method as in Synthesis Example 1. The results confirmed the presence of potassium at 1700 ppm as a countercation.

[0161] (Synthesis Example 4_Graphene Materials-4)

[0162] At room temperature (25°C) and in a nitrogen environment, 4g of natural graphite (F#1, manufactured by Nippon Graphite Industries, Ltd., average particle size 350μm), 8g of lithium citrate, and 25ml of IPA were weighed and pulverized using a planetary ball mill (manufactured by Feichi Corporation, model: P-6, ball diameter 10mm, speed 540rpm) for 40 minutes. After washing with deionized water and filtering, the pulverized material was dried at 60°C to obtain graphene material-4.

[0163] The target cation was quantitatively analyzed using the same method as in Synthesis Example 1. The results confirmed the presence of lithium element at 2800 ppm by mass as a countercation.

[0164] <Preparation of Carbon Composite Active Material Materials>

[0165] (For making Example 1_Example 1)

[0166] 0.02 g of binder (carboxymethyl cellulose (CMC)) was added to 100 g of a deionized water / IPA solution composed of isopropanol and deionized water and dispersed. Then, 0.65 g of graphene material-1 was added and ultrasonically dispersed. The mixture was then centrifuged to prepare a graphene dispersion. 150 g of positive electrode active material (lithium nickelate) was mixed into the graphene dispersion, filtered, and dried to obtain carbon composite active material-1. The graphene content in carbon composite active material-1 was 0.26% by mass, and the binder content was 0.01% by mass.

[0167] (For making Example 2_Example 2)

[0168] The amount of binder (carboxymethyl cellulose (CMC)) was set to 0.09 g, and graphene material-2 was used instead of graphene material-1, with the amount of graphene material-2 set to 3.32 g. Otherwise, the process was carried out in the same manner as in Example 1 to obtain carbon composite active material-2. The graphene content in carbon composite active material-2 was 1.29% by mass, and the binder content was 0.05% by mass.

[0169] (For making Example 3_Example 3)

[0170] The amount of binder (carboxymethyl cellulose (CMC)) was set to 0.01 g, and graphene material-3 was used instead of graphene material-1, with the amount of graphene material-3 set to 0.36 g. Otherwise, carbon composite active material-3 was obtained by the same method as in Example 1. The graphene content in carbon composite active material-3 was 0.14% by mass, and the binder content was 0.01% by mass.

[0171] (For making Example 4_Example 4)

[0172] The amount of binder (carboxymethyl cellulose (CMC)) was set to 0.02 g, and graphene material-3 was used instead of graphene material-1, with the amount of graphene material-3 set to 0.74 g. Otherwise, carbon composite active material-4 was obtained by the same method as in Example 1. The graphene content in carbon composite active material-4 was 0.32% by mass, and the binder content was 0.01% by mass.

[0173] (For making Example 5_Example 5)

[0174] The amount of binder (carboxymethyl cellulose (CMC)) was set to 0.12 g, and graphene material-4 was used instead of graphene material-1, with the amount of graphene material-4 set to 5.85 g. Otherwise, carbon composite active material-5 was obtained by the same method as in Example 1. The graphene content in carbon composite active material-5 was 1.74% by mass, and the binder content was 0.06% by mass.

[0175] (For making Example 6_Example 6)

[0176] The amount of binder (carboxymethyl cellulose (CMC)) was set to 0.12 g, and the amount of graphene material-1 was set to 7.54 g. Otherwise, carbon composite active material-6 was obtained by the same method as in Example 1. The graphene content in carbon composite active material-6 was 1.87% by mass, and the binder content was 0.23% by mass.

[0177] (For use in Example 7 - Example 7)

[0178] The amount of binder (carboxymethyl cellulose (CMC)) was set to 1.19 g, and graphene material-3 was used instead of graphene material-1, with the amount of graphene material-3 set to 8.36 g. Otherwise, carbon composite active material-7 was obtained by the same method as in Example 1. The graphene content in carbon composite active material-7 was 1.95% by mass, and the binder content was 0.65% by mass.

[0179] (For making Example 8 and comparing it with Example 2)

[0180] The amount of binder (carboxymethyl cellulose (CMC)) was set to 0.15 g, and graphene material-3 was used instead of graphene material-1, with the amount of graphene material-3 set to 9.40 g. Otherwise, carbon composite active material-8 was obtained by the same method as in Example 1. The graphene content in carbon composite active material-8 was 2.22% by mass, and the binder content was 0.08% by mass.

[0181] (For making Example 9 and comparing it with Example 3)

[0182] The amount of binder (carboxymethyl cellulose (CMC)) was set to 1.30 g, and graphene material-3 was used instead of graphene material-1, with the amount of graphene material-3 set to 4.01 g. Otherwise, carbon composite active material-9 was obtained by the same method as in Example 1. The graphene content in carbon composite active material-9 was 1.03% by mass, and the binder content was 0.77% by mass.

[0183] (For making Example 10 and comparing it with Example 4)

[0184] The amount of binder (carboxymethyl cellulose (CMC)) was set to 0.08 g, and acetylene black (Li-100, manufactured by Denka Company Limited) was used instead of graphene material, with an amount set to 0.45 g. Otherwise, carbon composite active material material-10 was obtained by the same method as in Example 1. The carbon content in carbon composite active material material-10 was 0.19% by mass, and the binder content was 0.04% by mass.

[0185] < Peak intensity ratio of graphene materials (I D / I G >

[0186] Using graphene materials 1 through 4 and acetylene black as the testing powders, the peak intensity ratio (I) of the graphene materials was calculated using the following method. D / I G The calculated results are shown in Table 1 (Examples 1-7) and Table 2 (Comparative Examples 1-4).

[0187] 0.3 g of the test powder was added to 100 mL of a mixed solvent of deionized water and IPA (volume ratio: 60 / 40). The mixture was ultrasonically homogenized for 3 minutes using an ultrasonic homogenizer (UH-600S, SMT Corporation, 26 mm Φ) to prepare a dispersion with a solid content of 3 g / L. 100 mL of this dispersion was transferred to two 50 mL centrifuge tubes and centrifuged for 10 minutes at 25°C and 1000 rpm using a centrifuge (CR21N, Hitachi Koki Corporation). The supernatant of the centrifuged dispersion was dripped onto a 5 μm membrane filter for filtration. The sample on the membrane filter was subjected to Raman spectroscopy using a laser Raman spectrometer (HR-800, Horiba Corporation). The measurement conditions were: laser wavelength 514.79 nm and wavenumber 100–4000 cm⁻¹. -1 .

[0188] The obtained spectrophotometers are located in the 1300–1400 cm⁻¹ range. -1 The peak intensity of the D band within the range of I D and in the range of 1550-1650cm -1 The peak intensity of the G-band within the range of I G Calculate the peak intensity ratio (I) D / I G ).

[0189] <DG / DA>

[0190] After the carbon composite active material was embedded in a thermosetting resin, it was processed into thin sheets. The cross-section of the particles was observed using an atomic resolution analytical electron microscope (JEM-ARM200F NEOARM manufactured by Nippon Electron Co., Ltd.). The size of the graphene particles attached to the surface of the active material particles was randomly measured at 20 locations, and the average value was set as DG (μm).

[0191] The lengths (major axis, μm) of the longest part and the shortest part (minor axis, μm) of 20 electrode active material particles were randomly measured using a scanning electron microscope (Hitachi High Technology Co., Ltd., model S-3400NX). The average of the 20 values ​​calculated by (major axis + minor axis) / 2 was set as DA (μm).

[0192] <Making a Secondary Battery>

[0193] (Example 1)

[0194] (1) Preparation of positive electrode slurry

[0195] Carbon composite active material-1, acetylene black as a conductive additive, carbon nanotubes, and polyvinylidene fluoride (PVDF) as a binder were added to N-methylpyrrolidone (NMP) in a mass ratio of lithium nickelate:acetylene black:carbon nanotubes:PVDF=92:2:2:4. The positive electrode slurry was prepared by stirring in a FILMIX mixer (model: 80, manufactured by PRIMIX Co., Ltd.) at a speed of 20 m / s for 15 minutes.

[0196] (2) Preparation of negative electrode paste

[0197] Spherical graphite (as the negative electrode active material), Si, graphite (as a conductive additive), and carboxymethyl cellulose (CMC) (as a binder) were added to a mixed solvent containing deionized water and 2-propanol (IPA) in a volume ratio of 6:4 at a mass ratio of graphite:Si:graphite:CMC=80:12:4:4. The mixture was stirred for 30 minutes at a speed of 30 m / s using a FILMIX mixer (model: 80, manufactured by FILMIX Corporation) to prepare a negative electrode slurry.

[0198] (3) Fabrication of negative and positive electrodes

[0199] Using a rod coater (IMC-7000, manufactured by Imoto Manufacturing Co., Ltd.), the prepared negative and positive electrode slurries were coated onto one side of the current collector foil (SUS foil). The coated current collector foil was then dried at 85°C for 24 hours using an explosion-proof dryer (SAFWTY OVEN SPHH-100, manufactured by ESPEC CORP., Japan) to produce the negative and positive electrodes.

[0200] (4) Manufacturing of battery components

[0201] The dried negative and positive electrodes were rolled separately using a heated small-scale rolling mill (R-THCH1516, manufactured by THANK METAL CO.,LTD.), and then punched into 16mm diameter pieces. .

[0202] As battery components, the above-mentioned positive electrode, the above-mentioned negative electrode, and a spacer (Ube Maxell CPORE (registered trademark) / thickness 0.025mm / 19.5mm) are prepared. The coin batteries were dried in the transition chamber of the glove box (UNICO / UN-1000L) at a temperature of 85°C and a pressure of -0.1MPa.

[0203] (5) Battery manufacturing

[0204] After drying, the battery components were transferred from the glove box's transfer compartment to the main box. The negative and positive electrodes were overlapped in the coin cell, separated by a spacer. 1 mL of electrolyte was injected, and the coin cell was sealed using a manual coin cell sealing machine, thus producing a CR2032 type coin cell (Battery-1). The produced battery was then removed from the glove box. It should be noted that the electrolyte used was a non-aqueous electrolyte formed by dissolving lithium hexafluorophosphate (LiPF6) at a concentration of 1 mol / L in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) with a volume ratio of EC:DEC = 50:50.

[0205] (Example 2)

[0206] In the preparation of the positive electrode slurry, carbon composite active material material-2 was used instead of carbon composite active material material-1. Otherwise, battery-2 was prepared by the same method as in Example 1.

[0207] (Example 3)

[0208] In the preparation of the positive electrode slurry, carbon composite active material-3 was used instead of carbon composite active material-1. Otherwise, battery-3 was prepared by the same method as in Example 1.

[0209] (Example 4)

[0210] In the preparation of the positive electrode slurry, carbon composite active material-4 was used instead of carbon composite active material-1. Otherwise, battery-4 was prepared by the same method as in Example 1.

[0211] (Example 5)

[0212] In the preparation of the positive electrode slurry, carbon composite active material-5 was used instead of carbon composite active material-1. Otherwise, battery-5 was prepared by the same method as in Example 1.

[0213] (Example 6)

[0214] In the preparation of the positive electrode slurry, carbon composite active material-6 was used instead of carbon composite active material-1. Otherwise, battery-6 was prepared by the same method as in Example 1.

[0215] (Example 7)

[0216] In the preparation of the positive electrode slurry, carbon composite active material material-7 was used instead of carbon composite active material material-1. Otherwise, battery-7 was prepared by the same method as in Example 1.

[0217] (Comparative Example 1)

[0218] In the preparation of the positive electrode slurry, untreated positive electrode active material was used instead of carbon composite active material material-1. Otherwise, battery-8 was prepared by the same method as in Example 1.

[0219] (Comparative Example 2)

[0220] In the preparation of the positive electrode slurry, carbon composite active material material-8 was used instead of carbon composite active material material-1. Otherwise, battery-9 was prepared by the same method as in Example 1.

[0221] (Comparative Example 3)

[0222] In the preparation of the positive electrode slurry, carbon composite active material-9 was used instead of carbon composite active material-1. Otherwise, battery-10 was prepared by the same method as in Example 1.

[0223] (Comparative Example 4)

[0224] In the preparation of the positive electrode slurry, carbon composite active material-10 was used instead of carbon composite active material-1. Otherwise, battery-11 was prepared by the same method as in Example 1.

[0225] <Capacity retention rate>

[0226] The batteries-1 to-11 produced in each embodiment and comparative example were subjected to charge-discharge tests using a charge-discharge tester (TOSCAT-3100 manufactured by Toyo Systems Co., Ltd.).

[0227] Regarding charging, the upper limit voltage is set to 4.2V with the open circuit voltage (OCV) as the starting point in a constant temperature bath at 25℃. After charging in constant current (CC) mode at 0.1C, charging is then carried out in constant voltage (CV) mode with a cutoff current of 0.01C.

[0228] Regarding discharge, the lower limit voltage was set to 2.0V, and the temperature of the constant temperature bath was maintained at 25℃. Discharges were performed at 0.1C and 5.0C. The ratio of the discharge capacity at this time was calculated as (discharge capacity at 5C rate / discharge capacity at 0.5C rate) × 100, which was taken as the capacity retention rate at 5C rate.

[0229] Based on the above measurement results, the electrodes were evaluated according to the following evaluation criteria. The results are shown in Table 1 (Examples 1-7) and Table 2 (Comparative Examples 1-4).

[0230] [Evaluation Criteria]

[0231] ◎: The capacity retention rate at 5C is over 70%.

[0232] ○: The capacity retention rate at 5C is over 60.4% and less than 70%.

[0233] ×: The capacity retention rate at 5C is below 60.4%.

[0234] [Table 1]

[0235] [Table 2]

[0236] It was confirmed that the batteries with electrodes of Examples 1 to 7, i.e., electrodes made of slurry containing specific carbon composite active material, all had a capacity retention rate greater than the baseline value (60.4%) at 5C rate, and the rate performance was improved.

[0237] Industrial applicability

[0238] The carbon composite active material disclosed herein is suitable for use as an active material for electrodes in secondary batteries where improved rate performance is required.

Claims

1. A carbon composite active material having particles of electrode active material and a surface layer coating the particles, wherein, The surface layer is composed of a coating material containing graphene material and a binder. The graphene material contains anionic functional groups and countercations of these anionic functional groups at its ends, and the peak intensities of the D and G bands in the Raman spectra obtained by Raman spectroscopy are I... D / I G It is below 0.

50. In the carbon composite active material, the graphene content is 0.1 to 2.2% by mass, and the binder content is 0.01 to 0.7% by mass.

2. The carbon composite active material according to claim 1, wherein, The ratio of the graphene material to the binder, by mass, is 3 to 30.

3. The carbon composite active material according to claim 1 or 2, wherein, The ratio of the planar dimension DG of the graphene material to the particle size DA of the electrode active material, DG / DA, is 0.002 to 3.

000.

4. The carbon composite active material according to any one of claims 1 to 3, wherein, The electrode active material is a positive electrode active material.

5. The carbon composite active material according to any one of claims 1 to 4, wherein, The electrode active material is a negative electrode active material.

6. The carbon composite active material according to claim 4, wherein, The positive electrode active material is a lithium-containing composite oxide.

7. The carbon composite active material according to claim 6, wherein, The lithium-containing composite oxide has at least one crystal structure selected from the group consisting of olivine, layered rock salt, and spinel.

8. The carbon composite active material according to claim 5, wherein, The negative electrode active material is selected from graphite, SiO2, etc. x And at least one of the groups consisting of lithium titanate, wherein 0 ≤ x < 2.

9. The carbon composite active material according to any one of claims 1 to 8, wherein, The adhesive comprises at least one selected from the group consisting of fluorinated resins, olefin resins, vinyl resins, polyamides, polyimides, polyethers, polysaccharides, and rubbers.

10. An electrode, wherein, It is formed using a slurry containing any one of the carbon composite active materials according to claims 1 to 9.

11. A secondary battery, wherein, It has the electrode as described in claim 10.

Citation Information

Patent Citations

  • Positive electrode active material and nonaqueous electrolytic battery

    JP2002110162A

  • Manufacturing method of positive electrode

    JP2020021745A